2016
DOI: 10.1128/aem.01159-16
|View full text |Cite
|
Sign up to set email alerts
|

Development of a CRISPR-Cas9 Tool Kit for Comprehensive Engineering of Bacillus subtilis

Abstract: The establishment of a clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 system for strain construction in Bacillus subtilis is essential for its progression toward industrial utility. Here we outline the development of a CRISPR-Cas9 tool kit for comprehensive genetic engineering in B. subtilis. In addition to site-specific mutation and gene insertion, our approach enables continuous genome editing and multiplexing and is extended to CRISPR interference (CRISPRi) for transcriptional modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(168 citation statements)
references
References 81 publications
2
156
0
4
Order By: Relevance
“…Our initial genetic analysis resulted in the creation of a CRISPR/Cas9 genome editing system on a single, temperaturesensitive plasmid that results in markerless mutations that can be quickly introduced into many genetic backgrounds. Although this is not the first report of CRISPR/Cas9 genome editing in Bacillus subtilis (50,51), the system described here does not require an inducer for Cas9 expression and still allows for efficient removal of the plasmid editing system. We further demonstrated that the novel mutS2 phenotype depends on recA and does not depend on uvrA or recU.…”
Section: Discussionmentioning
confidence: 97%
“…Our initial genetic analysis resulted in the creation of a CRISPR/Cas9 genome editing system on a single, temperaturesensitive plasmid that results in markerless mutations that can be quickly introduced into many genetic backgrounds. Although this is not the first report of CRISPR/Cas9 genome editing in Bacillus subtilis (50,51), the system described here does not require an inducer for Cas9 expression and still allows for efficient removal of the plasmid editing system. We further demonstrated that the novel mutS2 phenotype depends on recA and does not depend on uvrA or recU.…”
Section: Discussionmentioning
confidence: 97%
“…CRISPRi holds great promise for a wide range of applications in microorganisms, including bacterial cell growth control [35], genetic screen [25, 36], synthetic biology module development [37, 38] or metabolic networks control in various microorganisms such as E. coli [24, 39, 40], mycobacteria [41], Bacillus subtilis [42], Corynebacterium glutamicum [43], Clostridium beijerinckii [44], yeast [45] and cyanobacteria [7]. In particular, a number of recent studies have exploited CRISPRi to regulate the metabolic pathways in E. coli for enhanced production of various biotechnological products including poly(3-hydroxybutyrate- co -4-hydroxybutyrate) [23], terpenoid [8], pinosylvin [46], flavonoid [47] and mevalonate [48].…”
Section: Discussionmentioning
confidence: 99%
“…pAW005 is a pHT01 (Nguyen, Phan, & Schumann, 2007) derivative containing a multiple cloning site (MCS) comprised of BamHI-AatII-SbfI-AscI and SpeI-NgoMIV-NotI-AsiSI-AgeI-XmaI restriction sites flanking promoter P grac.max , a modified version of P grac (i.e., promoter P01) (Phan, Nguyen, & Schumann, 2012). This cassette was inserted into SbfI/NheI-digested pAW004-2 (Westbrook et al, 2016), yielding pAW002-4. P grac.max contains the upstream promoter element (UP) of promoter P64, the −35 region of promoter P71, the −15 region of promoter P57, the native −10 region, and a T-C substitution at the +3 site (Phan et al, 2012).…”
Section: Plasmid Construction and Transformationmentioning
confidence: 99%
“…Mutation of clsA or pssA, encoding phosphatidylserine synthase (PssA), significantly increased extracellular amylase production, presumably through creating a more negative membrane charge density (Cao et al, 2017). To further enhance the functional expression of SeHAS, we then altered the distribution of CL in the membrane by reducing the expression of ftsZ via CRISPR interference (CRISPRi) using our recently developed CRISPR-Cas9 toolkit for B. subtilis (Westbrook et al, 2016). The membrane CL content was increased by overexpressing pgsA and clsA, resulting in significant improvements to the HA titer and MW.…”
Section: Introductionmentioning
confidence: 99%